Pengaruh Gaya Hidup, Kesadaran Halal, dan Word of Mouth Terhadap Keputusan Pembelian Steak Moen-Moen di Kota Depok - Hamidah Hamidah; Abdi Triyanto; Mustafa Kamal (Prodi Manajemen Bisnis Syariah, 2025)
AbstractThis study aims to determine the effect of lifestyle, halal awareness, and word of mouth on purchasing decisions for moen-moen steak in Depok city, using primary data with questionnaires distributed to Muslim communities aged ≥ 17 years who have bought and consumed moen-moen steak products at Depok city branches. The sampling technique used non-probability sampling techniques with a purposive sampling approach. Respondents in this study totaled 115 respondents. The data analysis technique uses the SEM-PLS method with the help of SmartPLS 4.1.0.8 software. The results of this study state that partially halal awareness and word of mouth have a significant positive effect on purchasing decisions, while lifestyle has no significant positive effect on purchasing decisions. Lifestyle, halal awareness, and word of mouth together (simultaneously) have a significant positive effect on purchasing decisions for Moen-Moen Steak in Depok city.